Content and quality of protein in proso millet (Panicum miliaceum L.) varieties - Kalinová, Jana; Moudrý, Jan (Plant foods for human nutrition, 2006)
Proso millet belongs to the oldest cereals that human is using. Eight varieties of proso millet were cultivated in Ceske Budejovice from 1998 to 2000 and Cerveny Dvur from 1999 to 2000. The crude protein content was determined according to Kjehladl method and amino acid content was determined chromatographically after acid and oxidative acid hydrolysis. Although the protein content of proso (11.6% of dry matter) was similar to wheat, the grain of proso was significant richer in essential amino acids (leucine, isoleucine, methionine) then wheat. Hence, the protein quality of proso (Essential Amino Acid Index) was higher (51%) compared to wheat. The proso grain contained about 3.3 g kg(-1) of the limiting amino acid-lysine. Significant differences in protein and its quality were found among the evaluated proso varieties. The varieties Toldanskoe and Lipetskoe were the most different from the others in protein and amino acid content and Amino Acid Score of individual acids. They had the lowest content and quality of protein. The seed coat of these varieties was red. The amino acid and protein content was significantly influenced by weather during the year. Dry conditions caused an increase of protein but its quality was decreased.
Keywords: déšť; Triticum; aminokyseliny; Quality Control; řízení kvality; dietní proteiny; pšenice; Panicum; Weather; počasí; Nutritive Value; nutriční hodnota; lidé; Humans; Financing, Organized; Rain; proso; financování organizované; Dietary Proteins; Amino Acids